Electroconvulsive Treatment: Hypotheses about Mechanisms of Action - Fosse, Roar; Read, John (Frontiers in Psychiatry, 2013)
No consensus has been reached on the mode of action of electroconvulsive treatment (ECT). We suggest that two features may aid in the delineation of the involved mechanisms. First, when effective, ECT would be likely to affect brain functions that are typically altered in its primary recipient group, people with severe depression. Central among these are the frontal and temporal lobes, the hypothalamus-pituitary-adrenal (HPA) stress axis, and the mesocorticolimbic dopamine system. Second, the involved mechanisms should be affected for a time period that matches the average endurance of clinical effects, which is indicated to be several days to a few weeks. To identify effects upon frontal and temporal lobe functioning we reviewed human studies using EEG, PET, SPECT, and fMRI. Effects upon the HPA axis and the dopamine system were assessed by reviewing both human and animal studies. The EEG studies indicate that ECT decelerates neural activity in the frontal and temporal lobes (increased delta and theta wave activity) for weeks to months. Comparable findings are reported from PET and SPECT studies, with reduced cerebral blood flow (functional deactivation) for weeks to months after treatment. The EEG deceleration and functional deactivation following ECT are statistically associated with reduced depression scores. FMRI studies indicate that ECT flattens the pattern of activation and deactivation that is associated with cognitive task performance and alters cortical functional connectivity in the ultra slow frequency range. A common finding from human and animal studies is that electroconvulsive treatment acutely activates both the HPA axis and the dopamine system. In considering this evidence, we hypothesize that ECT affects the brain in a similar manner as severe stress or brain trauma which activates the HPA axis and the dopamine system and may compromise frontotemporal functions.